4-H Afterschool Resource Guide: Teens as Volunteer Leaders - Sharon K. Junge; Vanessa Spero; Niki Crawson; J. R. Davis; Tara Dorn; Beth Rasa Edwards; Stacy Hall; Karen Henry; Heather Janney; Beth Kerr; Andrea Lazzari; Abby Morgan; et al. (EDIS, 2023)
This resource guide is designed to be used by Extension/4-H professionals to deliver teen-led curricula in after-school programs. It includes an overview of program delivery, recruitment processes and training outlines. The original educational material was edited and revised for this edition by the National Association of 4-H Youth Development Professionals Afterschool Working Group, led by Vanessa Spero. Published by the 4-H Youth Development Department, UF/IFAS Extension, April 2023.